First report of Alternaria leaf blight disease on oil palm caused by Alternaria longipes in Thailand - Nakarin Suwannarach (2018)
© 2014, Springer Science+Business Media Dordrecht. A leaf blight on oil palm, caused by Alternaria longipes, was found in an Elaeis guineensis plantation for the first time in Chiang Mai Province, Thailand. The fungus was isolated from the lesions and its pathogenicity was confirmed. The fungus was identified based on morphological characteristics and confirmed using comparisons of DNA sequences of internal transcribed spacer (ITS) regions 1 and 2 plus 5.8S rDNA. This report is the first on oil palm leaf blight disease caused by A. longipes.